Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

Listen carefully. Tread lightly. Adapt quickly. Approaching Adaptive Management: Examples from our Somalia Education Programming - CARE (CARE Learning, 2020)
Adaptive management approaches potentially offer us opportunities to deliver high quality results in circumstances where change is complex, including in fragile, unstable or conflict affected places. However, building adaptive programming continues to be a challenge for the sector. For CARE, our Department for International Development -UK Aid funded Girls’ Education Challenge (GEC) programming has provided useful learning on how to operationalise adaptive approaches. In this paper we expand on our learning from this project and offer some recommendations for how to create more opportunities for truly adaptive programming in the future. In particular: • Projects that are designed to adapt need budget structures, results frameworks and governance that enable the process of adaptation. In our GEC projects the approaches employed by DFID, including the introduction of Review and Adaptation meetings have served to support meaningful adaptation. • Adaptive projects require both strong participatory elements and flexible governance and accountability structures. Whilst rigorous and comprehensive Monitoring, Evaluation and Learning (MEL) systems are important without these other elements appropriate adaptation can be hindered. • Adaptive Management requires resources. Where the expected change is complex, adaptation is frequently necessary to ensure we are responding to context and evidence. This should be adequately resourced if we are to expect results. In an environment where many INGOs work consistently within complex environments, the sector also needs more opportunities to trial these approaches and could benefit from more funding streams available which include the kinds of approaches used by DFID in current GEC programming

Monitoring for problem-solving, adaptive management, reporting and learning - Dominique Morel; Dzino-Silajdzic, Velida; Hagens, Clara (Catholic Relief Services, 2020)
Internal and external stakeholders have different information needs over a project’s life, for purposes that include adaptive management, accountability, compliance, reporting and learning. A project’s monitoring, evaluation, accountability and learning, or MEAL, system should provide the information needed by these stakeholders at the level of statistical reliability, detail and timing appropriate to inform data use. In emergency contexts where the situation is still fluid, ‘informal monitoring’ has proved helpful to staff’s ongoing assessment of the broader environment in order to identify changes in the situation, in other actors’ responses, and in priority unmet needs that would require corresponding changes in the response.2 The same distinction between informal monitoring of possible changes in the project’s operating context—whether identified as project assumptions and risk factors or not—and formal monitoring of the activities included in the response and project indicators, is relevant for development contexts too. Informal monitoring: Ongoing assessment of changes in operating context Formal monitoring: Tracking progress against project activities and indicators Within formal monitoring, it is useful to further differentiate between light monitoring and rigorous monitoring: - Light monitoring aims to provide timely feedback on new activities (or new locations or target groups) or aspects of the project’s theory of change (activity-to-output or output-to-IR change) logic that staff are less confident about, to check for early signs that progress is being made and that assumptions are holding true while there is still ample time to make adjustments if necessary.3 - Rigorous monitoring aims to collect representative data for evidence-based project management, reporting and learning, not just at midterm but throughout project implementation.

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

Physically distanced adaptive management - Proud, Emma (LearnAdapt, 2020)
Opportunities and challenges for local leadership

Diseño transformacional de proyectos - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

Evaluation of International Development Interventions: An Overview of Approaches and Methods - Vaessen, Jos; Lemire, Sebastian; Befani, Barbara (World Bank, 2020)
This guide provides an introductory overview of a range of methods that have been selected for their actual and potential use in the field of international development evaluation. For each method, a detailed guidance note presents the method’s main features and procedural steps, key advantages and disadvantages, as well as its applicability. Each guidance note includes references for relevant background readings (basic and advanced) as well as references to other additional resources of interest. Both the choice of approaches and methods and the associated guidance are by no means definitive. IEG plans to periodically update the guide as evaluation practices evolve.

A Pragmatic Approach to Assessing System Change: How to put it into practice - Miehlbradt, Alexandra; Shah, Rachel; Posthumus, Hans; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.